Bullous Tinea Pedis – Misdiagnosed for Long Time (Community Based Medical Journal, 2017)
Fungal infection is very common in Dermatological practice in Bangladesh. Most of the cases can be diagnosed clinically and simple laboratory examination. But here we present a case of recurrent bullous tinea pedis that had been misdiagnosed for a long time and treated with oral steroids. Initially, direct microscopy of potassium hydroxide preparations was negative and culture did not reveal any fungal organism. In a biopsy taken simultaneously from the edge of a bulla and stained with periodic acid-Schiff, septate mycelia were clearly visible. Trichophyton mentagrophytes was later identified in repeated cultures. The patient was treated with oral Terbinafine 250 mg daily for 2 months cured completely.CBMJ 2017 January: Vol. 06 No. 01 P: 28-30